Infrastructure and trade: A gravity analysis for major trade categories using a new index of infrastructure - Julian Donaubauer; Alexander Glas; Peter Nunnenkamp (Kiel Institute for the World Economy (IfW), 2015)
Making use of considerably improved measures of infrastructure, we assess the impact of infrastructure on bilateral trade for a panel of 37 developed and emerging economies during the period 1995-2011. We find significant and non-linear effects of overall infrastructure and infrastructure in transportation, communication, energy, and finance on trade in consumption goods, capital goods, and intermediates. Our major findings prove to be robust to various modifications and extensions of the gravity model. Importantly, we still observe significant and non-linear effects of infrastructure on bilateral trade after accounting for potential reverse causality.
Keywords: F14; O18; 330; trade; infrastructure; transport; ICT; energy; finance